1987
DOI: 10.3109/00016348709083027
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vaginal Secretory Immunoglobulin a, Gardnerella Vaginalis, Anaerobes, and Chlamydia Trachomatis in Post Abort al Pelvic Inflammatory Disease

Abstract: In a prospective study of 129 women undergoing induced first-trimester abortion, 14 (10.9%) contracted postabortal pelvic inflammatory disease (PID). Samples of vaginal secretion for quantitation of secretory immunoglobulin A (sIgA) as well as isolates from cervix/urethra for the culture of anaerobes and aerobes, including Bacteroides fragilis et melaninogenicus and Gardnerella vaginalis, were obtained at the preoperative visit. Two blood samples from each woman with postabortal PID were analysed for antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
4
6
1
Order By: Relevance
“…Others have reported similar findings (82,106,117). In another study (71), postabortal pelvic inflammatory disease occurred in 9 (25%) of 36 women who had vaginitis during the previous year compared with 4 (5%) of 74 without prior vaginitis (P < 0.005). Association with specific organisms from cervical cultures collected at the time of pelvic inflammatory disease could not be made.…”
Section: Gas-liquid Chromatographysupporting
confidence: 67%
“…Others have reported similar findings (82,106,117). In another study (71), postabortal pelvic inflammatory disease occurred in 9 (25%) of 36 women who had vaginitis during the previous year compared with 4 (5%) of 74 without prior vaginitis (P < 0.005). Association with specific organisms from cervical cultures collected at the time of pelvic inflammatory disease could not be made.…”
Section: Gas-liquid Chromatographysupporting
confidence: 67%
“…Osser and Persson [7] found that local IgA antibodies offered no protection against salpingitis and probably also endometritis. Heisterberg et al [17] came to the same conclusions. Brunham et al [6] demonstrated an inverse correlation with S-IgA and recovery of C trachomatis from the cervix.…”
Section: Discussionsupporting
confidence: 70%
“…Information on treatment for Chlamydia-positive women was not available in the 1987 study by Heisterberg et al [44], and only results for Chlamydia negative women, who did not receive prophylaxis, were included in four other studies [36,41,49,50]. Among women randomized to receive antibiotic prophylaxis in three RCTs [35,37,42], there was a lower incidence of PID at follow-up (4.8-5.5%) than for women assigned to the control group (8.6-10.9%).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 9 Although the majority of studies reported on multiple interventions for minor and major complications, one study reported on every outcome considered in this review [20]; six studies only had information on treatment for infection [37,38,41,44,50,61] and two only reported on interventions for anesthesia-related complications [31,68]. The inclusion and exclusion criteria were clearly defined, but several studies reported excluding women who tested positive for a sexually transmitted infection or recently had been treated with antibiotics.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%